Entangled fields. Sources and hypotheses for the history of Afro-Brazilian, African-American and african studies in Brazil and the United States - Livio Sansone (Cahiers des Amériques Latines)
This exploratory article results from research still in progress in a set of archives in the US and deals with the thematic and biographic entangled history of African-American, Afro-Brazilian and African studies carried out in the US and Brazil in the period roughly corresponding to three decades, 1940-1970. It focuses on two important and original characters, Melville J. Herskovits and Eduardo Chivambo Mondlane, and argues that a perspective emphasizing both the history of institutions and individual trajectories or biographies might elicit interesting new details that might otherwise remain underlit.